Volatility Transmission between Oil Price and Exchange Rate - Hamida, Arafet; Nasr, Salah ben (International Journal of Energy Economics and Policy, 2024)
This article presents a study on the transmission of oil price volatility to the exchange rates of 14 countries (net oil exporters and importers) during the period from 02/01/2000 to 31/11/2022. The aim is to compare the effect of oil price fluctuations on exchange rate volatility based on the country’s nature. Using ARCH, GARCH, and GARCH-BEKK models, our results reveal that the real effective exchange rate is significantly linked to fluctuations in the real oil price for both categories of countries: oil importers and exporters. These findings have important implications for monetary, fiscal, inflationary, and trade policies for these countries.